Detecting tropical wildlife declines through camera-trap monitoring: an evaluation of the Tropical Ecology Assessment and Monitoring protocol. Issue 1 (10th September 2018) - Beaudrot, Lydia; Ahumada, Jorge; O'Brien, Timothy G.; Jansen, Patrick A.
Abstract: Identifying optimal sampling designs for detecting population-level declines is critical for optimizing expenditures by research and monitoring programmes. The Tropical Ecology Assessment and Monitoring (TEAM) network is the most extensive tropical camera-trap monitoring programme, but the effectiveness of its sampling protocol has not been rigorously assessed. Here, we assess the power and sensitivity of the programme's camera-trap monitoring protocol for detecting occupancy changes in unmarked populations using the freely available application PowerSensor! . We found that the protocol is well suited to detect moderate (≥ 5%) population changes within 3–4 years for relatively common species that have medium to high detection probabilities (i.e. p > 0.2). The TEAM protocol cannot, however, detect typical changes in rare and evasive species, a category into which many tropical species and many species of conservation concern fall. Additional research is needed to build occupancy models for detecting change in rare and elusive species when individuals are unmarked.